Environmental life cycle evaluation of prefabricated residential construction in China. (1st October 2022) - Tian, Yimeng; Spatari, Sabrina
Abstract: Due to rapid urbanization, the construction industry in China consumes a significant quantity of material and is responsible for considerable greenhouse gas emissions. Prefabricated construction methods are promoted by the Chinese government because of their potential environmental and economic benefits towards enhancing the productivity and quality of built structures and on-site construction-related pollution. This research investigates the environmental tradeoffs offered by prefabrication methods compared to traditional cast in-situ methods using life cycle assessment (LCA), focusing on primary non-renewable energy, global warming, terrestrial acidification, human carcinogenic toxicity, fine particulate matter formation and eutrophication using a cradle-to-final construction system boundary. Primary data collected from two residential projects under construction in 2019–2020 and built by prefabrication and traditional construction methods in China were compared. This study investigates parameter uncertainty on regional greenhouse gas (GHG) emissions related to electricity production. The results reveal that except for marine eutrophication, prefabrication methods offer more environmental advantages compared to traditional methods for all impact categories. The uncertainty analysis showed that the GHG emission factor for electricity production is not significant within the system boundary. Future research should investigate uncertainty among other parameters related to the building materials in the context of Chinese production. The findings of the study can provide a basis for policy makers in promoting sustainable construction in the context of China. Graphical abstract: Image 1 Highlights: Environmental impact of prefabricated and traditional construction evaluated in China. Projects were compared via multiple LCIA metrics. Parametric uncertainty evaluated for GHG emissions related to electricity. Prefabricated construction offers environmental benefits for most LCIA metrics.